Glycosylation and methylation in the biosynthesis of isoflavonoids in Pueraria lobata - Li, Changfu; Zhang, Yansheng (Frontiers in Plant Science, 2023)
The pathway for forming isoflavonoid skeletal skeletonstructureformation of isoflavonoid scaffold is predominantly primarily conserved inrestricted to the Leguminosae family. Subsequent decorations on the compound backbone by tailoring enzymes would change their biological and physicochemical medicinal properties of these molecules. Pueraria lobata is a leguminous plant, and as a traditional Chinese medicine its roots have been ascribed a number of pharmacological propertiesactivities. Glycosylation and methylation are the main modifying processes in isoflavonoid metabolism in P. lobata roots, resulting in the accumulation of unique glycosylated and methylated end isoflavonoid compounds. For instances, daidzein 8-C-glucoside (i.e., puerarin) and its the puerarin derivatives are produced only by the Pueraria genus. Puerarin has been developed established as a clinical drug for the treatment ofcuring cardiovascular diseases. To better understand the characteristic isoflavonoid metabolism in P. lobata, this review attempts to summarize the research progress made with understanding the main glycosylation and methylation of isoflavonoids in P. lobata and their biosynthetic enzymes.